Effect of a network system for providing proper inhalation technique by community pharmacists on clinical outcomes in COPD patients - Takemura M; Mitsui K; Ido M; Matsumoto M; Koyama M; Inoue D; Takamatsu K; Itotani R; Ishitoko M; Suzuki S; Aihara K; Sakuramoto M; et al. (International Journal of COPD, 2013)
Masaya Takemura,1 Katsumi Mitsui,2 Masako Ido,2 Masataka Matsumoto,1 Misuzu Koyama,3 Daiki Inoue,1 Kazufumi Takamatsu,1 Ryo Itotani,1 Manabu Ishitoko,1 Shinko Suzuki,1 Kensaku Aihara,1 Minoru Sakuramoto,1 Hitoshi Kagioka,1 Motonari Fukui11Respiratory Disease Center, Kitano-Hospital, the Tazuke Kofukai Medical Research Institute, Osaka, Japan; 2Division of Pharmacy, Kitano-Hospital, The Tazuke Kofukai Medical Research Institute, Osaka, Japan; 3Kita-ku Pharmaceutical Association, Osaka, JapanIntroduction: Nonadherence to inhalation therapy is very common in patients with chronic obstructive pulmonary disease (COPD). Few data are available to support the role of community pharmacists in optimizing inhalation therapy in COPD patients. Since 2007, the Kitano Hospital and the Kita-ku Pharmaceutical Association have provided a network system for delivering correct inhalation techniques through certified community pharmacists. The effects of this network system on clinical outcomes in COPD patients were examined.Methods: A total of 88 consecutive outpatients with COPD at baseline and 82 of those 4 years later were recruited from the respiratory clinic of Kitano Hospital Medical Research Institute. Measurements included the frequency of COPD exacerbations, patients’ adherence to inhalation therapy using a five-point Likert scale questionnaire, and patients’ health status both prior to this system and 4 years later.Results: Usable information was obtained from 55 patients with COPD at baseline, and from 51 patients 4 years later. Compared with baseline values, a significant decrease was observed in the frequency of COPD exacerbations (1.5 ± 1.6 versus 0.8 ± 1.4 times/year, P = 0.017). Adherence to the inhalation regimen increased significantly (4.1 ± 0.7 versus 4.4 ± 0.8, P = 0.024), but health status was unchanged. At 4 years, of 51 COPD patients, 39 (76%) patients who visited the certified pharmacies showed significantly higher medication adherence than those who did not (4.6 ± 0.6 versus 3.9 ± 1.0, P = 0.022).Conclusion: The network system may improve COPD control and adherence to inhalation regimens.Keywords: COPD, adherence, community pharmacist, exacerbation, quality of life